Maternal mosaicism for a second mutational event in a type I spinal muscular atrophy family. - Campbell, L (1998)
Spinal muscular atrophy (SMA) is a common fatal motor-neuron disorder characterized by degeneration of the anterior horn cells of the spinal cord, which results in proximal muscle weakness. Three forms of the disease, exhibiting differing phenotypic severity, map to chromosome 5q13 in a region of unusually high genomic variability. The SMA-determining gene (SMN) is deleted or rearranged in patients with SMA of all levels of severity. A high de novo mutation rate has been estimated for SMA, based on the deletion of multicopy microsatellite markers. We present a type I SMA family in which a mutant SMA chromosome has undergone a second mutation event. Both the occurrence of three affected siblings harboring this same mutation in one generation of this family and the obligate-carrier status of their mother indicate the existence of maternal germ-line mosaicism for cells carrying the second mutation. The existence of secondary mutational events and of germ-line mosaicism has implications for the counseling of SMA families undergoing prenatal genetic analysis.